To the Question of Interaction of Chuvash and Azerbaijan Cultures: Ancientry and Modernity - Vladimir A. Vasilyev (Publishing house "Sreda", 2021)
In the development of modern ethnic cultures, there is a paradoxical situation: the more powerful the onset of comprehensive globalization, aimed at the destruction of national cultures, the more actively they develop. "To blame", in our opinion, is the ethnocultural code, which rebelled against the dominance of the virus of the death of national cultures and thus led to the flourishing, boom of ethnic cultures. Convincing evidence of this is the deep fundamental processes of revival taking place in the Chuvash national culture. Thus, the unique Kokelev International Plein Air has rightfully become a synthesis of the picturesque national schools of Russia, Belarus and Ukraine. The national TV and radio company "Chavash En" was established. Recreated "Chuvashkino", designed to develop their national culture. There is a return from oblivion of the runic writing of the Chuvash people. A program for the development of the Chuvash language was adopted. And, as it were, the apotheosis of the renaissance of the Chuvash ethnic culture was the establishment of the Chuvash Embroidery Day on November 26 by the Decree of the Head of the Chuvash Republic. Globalization pressure is also causing an increase in interest in learning about other cultures. we tell about this phenomenon on the example of Chuvashia and Azerbaijan. In soviet times in Azerbaijan, few people knew that the Chuvash were a Turkic people. Tatarstan knew, Bashkortostan knew, and the Chuvash - the Turkic people - didn't [6]. The aim of our work is to study the interaction of Chuvash and Azerbaijani cultures in historical retrospect, as well as to draw the attention of scientists of Chuvashia, Russia and Azerbaijan to this problem, which is of great cognitive and scientific importance. The author comes to the conclusion that scientists-humanitarians of Chuvashia, Russia and Azerbaijan can and should combine their efforts to create a comprehensive study of the interaction of the cultures of the Chuvash and Azerbaijani nations in historical retrospect.